2016
DOI: 10.1039/c5ay03217b
|View full text |Cite
|
Sign up to set email alerts
|

pH-controlled sensitive and selective detection of Cr(iii) and Mn(ii) by using clove (S. aromaticum) reduced and stabilized silver nanospheres

Abstract: The colorimetric detection of Cr(iii) and Mn(ii) ions based on silver nanospheres (SNSs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Biofilm formation occurs rapidly in the environment (Lobelle and Cunliffe, 2011;Rummel et al, 2017), altering particle density and hydrophobicity and in turn increasing the rate of sinking. Microplastics may form aggregates with phytoplankton (Long et al, 2015) or marine snow (Porter et al, 2018;Zhao et al, 2016), flocculate and adhere to transparent exopolymers (Engel, 2004;Passow et al, 2001;Summers et al, 2018) or be incorporated into faecal pellets (Cole et al, 2016;Katija et al, 2017). In most cases these processes act to reduce the buoyancy of microplastics and thus increase the sinking rate, redistributing microplastics from surface waters to the ocean floor.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation occurs rapidly in the environment (Lobelle and Cunliffe, 2011;Rummel et al, 2017), altering particle density and hydrophobicity and in turn increasing the rate of sinking. Microplastics may form aggregates with phytoplankton (Long et al, 2015) or marine snow (Porter et al, 2018;Zhao et al, 2016), flocculate and adhere to transparent exopolymers (Engel, 2004;Passow et al, 2001;Summers et al, 2018) or be incorporated into faecal pellets (Cole et al, 2016;Katija et al, 2017). In most cases these processes act to reduce the buoyancy of microplastics and thus increase the sinking rate, redistributing microplastics from surface waters to the ocean floor.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles, on aggregation, display a visual color change which is useful for analysis without complex instruments . On the basis of aggregation mechanism, our research team reported many sensors by using nanoparticles and nanocomposites. Recently, we reported a selective and sensitive sensor for the detection of Cr 3+ and Mn 2+ ions, using green synthesized nanoparticles . There are many other reports on the colorimetric detection of metal ions. , However, to date, very limited reports are available for the detection of Al 3+ based on aggregation of AuNPs and none for the colorimetric detection of Al 3+ by AgNPs in an aqueous medium, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…18−20 Recently, we reported a selective and sensitive sensor for the detection of Cr 3+ and Mn 2+ ions, using green synthesized nanoparticles. 21 There are many other reports on the colorimetric detection of metal ions. 22,23 However, to date, very limited reports are available for the detection of Al 3+ based on aggregation of AuNPs 24−27 and none for the colorimetric detection of Al 3+ by AgNPs in an aqueous medium, to the best of our knowledge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nanoparticles of noble metals possess optical, chemical, electrochemical, and mechanical properties that make them ideal for various applications such as biocatalysis cosmetics, coating, and anticancer [9]. Recent developments such as paper-based analytical devices (PAD), colorimetric assays, quantumdots-based photoelectrochemical immune assays, magnetic bead-centered reverse colorimetric sensors, MnO 2 nanofakes with enzyme torrent intensifcation for colorimetric immunoassay, and Fenton reaction-centered colorimetric immunoassay have enabled colorimetric recognition in aqueous systems for metal ions [10][11][12][13][14][15][16][17][18][19][20][21][22]. Te accumulation of NPs induced by the target analyte is central to a graphic color alteration.…”
Section: Introductionmentioning
confidence: 99%